2002
DOI: 10.1023/a:1020238520948
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This presentation comprises a review on the use of immobilized algae for wastewater nitrogen, phosphorus and metal removal purposes. Details of the use of immobilized algae, the techniques of immobilization and the effects of immobilization on cell function are included. Particularly relevant in their use for heavy metal removal from wastewaters; upon enriching the biomass in metal, can be recoverd, thereby providing economic advantages. The use of immobilized microalgae in these processes is very adequate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(102 citation statements)
references
References 70 publications
0
101
0
1
Order By: Relevance
“…These data from a previous study reported by Takahashi et al [17]. 4 Standard value is not applied to coastal waters. 5 Standard value is applied to coastal waters.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These data from a previous study reported by Takahashi et al [17]. 4 Standard value is not applied to coastal waters. 5 Standard value is applied to coastal waters.…”
Section: Resultsmentioning
confidence: 98%
“…They have attracted attention equal to that devoted to seaweed products from several pharmaceutical, vitamin supplement, cosmetic and food companies [1,2] because these algae have functional materials that are rare among land plants. Moreover, other microalgae have attracted attention for use as biofuel materials [2,3] and bioremediation materials for environmental biodegradation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to the conventional treatment methods, microalgae are suggested to remove the nutrients from wastewater [35]. The use of microalgae or macro algae (seaweeds) to remove pollutants and nutrients from the wastewater is called phycoremediation.…”
Section: Environmental Pollutants Removing Through Microalgaementioning
confidence: 99%
“…Microalgae are used extensively in the treatment of waste waters because they can sequester large amounts of nutrients and other pollutants. At present, there are many municipal and industrial waste treatment plants that use microalgae in oxidation ponds to biodegrade wastes [35], [40] However, there is no control over the algal species and, with few exceptions, no harvesting of the algal biomass generated in these ponds.…”
Section: Introductionmentioning
confidence: 99%
“…As microalgas, pela extensa variedade de espécies e propriedades intrínsecas, demonstram grande potencial para exploração comercial. Dentre os principais componentes de suas células, destaca-se seu teor de lipídios, que é matéria prima para a produção de biodiesel (CAMPANELLA et al, 2001, MALLICK, 2002CHISTI, 2007;AMARO et al, 2012).…”
Section: Introductionunclassified